Analysis of the Causes of Duplicate Medical Records in the Health Recording System at the South Ponorogo Community Health Center Registration Desk - Hino Marga Yasa; Rumpiati Rumpiati (Garuda Pelamonia Jurnal Keperawatan, 2025)
Hino Marga Yasa, 2024 "Analysis of the causes of duplicate medical records in the health recording system." Scientific Paper, Supervising Lecturer (Rumpiati, S.ST., M.PH) DIII Medical Records and Health Informatics Study Program, STIKes Buana Husada Ponorogo. Duplicate medical records are a significant problem that can lead to data duplication, service disruptions, and patient misidentification errors. Double patient registration continues to occur at the South Ponorogo Health Centre, where this issue was discovered. The purpose of this study is to identify the causes of duplicate medical records and their impact on healthcare services. This study uses a qualitative research method alongside a descriptive method. Five registration clerks, the director of medical records, a reporting clerk, an IT clerk, and a nurse were interviewed, observed, and documented to collect data, according to registration staff. According to research findings, patients failing to carry their Medical Identification Cards (KIB), staff negligence, and limitations in the SIMRS search system all contribute to duplicate medical data. The number of cases reached 0.18%. In conclusion, to improve patient registration accuracy and reduce the likelihood of duplicate medical records, system updates, SOP enforcement, and staff competency development are necessary.